Računalniški program za uravnoteženje letala - Pavlin, Stanislav (Strojniški vestnik, 2004)
Aircraft balancing is an activity of great responsibility for the safety of aircraft in flying and landing. Usually aircraft balancing is made on air-carrier diagrams that are not unified. Regarding the planned total aircraft handling time, aircraft balancing requires great speed and, at the same time, great accuracy. A program has been developed at Airport Split for ramp handling control and aircraft balancing that fully complies with the standards defined in the International Air Transport Association document Airport Handling Manual. The program has been succesfully implemented at the following airports: Split, Dubrovnik, Pula, Zadar, Osijek and Knock (in Ireland) for air carriers and aircraft fleet landing at those airports, as well as the air carrier Air Zimbabwe. The new approach to the computer programfor aircraft balancing resulted in a universal program able to correspond with any air-carrier fleet. This computer program has been tested and approved by the following air carriers: Croatia Airlines, Adria Airways, Austrian Airlines, CSA, LOT, Malev, Lauda Air, Air Loyd, Fischer Air, Condor and Duo Airways.
Keywords: Laitila; letala; security; varnost; uravnoteženje; programi računalniški